Hits of the HOTS - Zulmy Faqihuddin Putera; Tutuk Widowati (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2021)
Abstract: To enhance his ability to solve problems, a student must acquire critical thinking skills. This article establishes the results of 5 higher order thinking skills (HOTS) problems tested to 24, ‘alumni’ of the 2013 Curriculum, students of the higher educational institution. The identification of critical thinking frameworks and the description of the critical thinking skills were based on the answers of 5 random samples. In general, students were characterized as critical thinking agents able to evaluate problems; HOTS were implemented by manufacturing information to determine choices; employing experience and transforming knowledge when working on solving problems resulted in 65.60% critical thinking skills representing the logic approvals of 56% information, 60% meaning, 96% model, 60% choice, and 56% reason through questionnaires and interviews.